2020
DOI: 10.18280/ijsse.100110
|View full text |Cite
|
Sign up to set email alerts
|

Using BIM for the Assessment of the Seismic Performance of Educational Buildings

Abstract: The progress of the study of seismic vulnerability has allowed the formulation of new assessment methodologies, which take into account not only the behaviour of the structural and non-structural elements, but also the components that, due to their importance and cost, can represent an investment that in some cases becomes greater than the cost of the whole building. To carry out this more specific type of study, it is necessary to use tools that allow estimating, locating and properly characterizing the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In particular, Jalaei and Jrade [50] have proposed a customized plug-in for Revit to facilitate the assessment of LEED indicators within a BIM environment. Additionally, BIM offers opportunities to manage the intrinsic complexity of a building supporting the development of seismic risk assessment procedures [51][52][53].…”
Section: Bim and Performance Assessmentmentioning
confidence: 99%
“…In particular, Jalaei and Jrade [50] have proposed a customized plug-in for Revit to facilitate the assessment of LEED indicators within a BIM environment. Additionally, BIM offers opportunities to manage the intrinsic complexity of a building supporting the development of seismic risk assessment procedures [51][52][53].…”
Section: Bim and Performance Assessmentmentioning
confidence: 99%
“…Recently, several studies have shown that the BIM platform can also be used in performance evaluation against destructive events such as earthquakes (Angulo et al , 2020). Therefore, Section 2.4 will evaluate the potential of BIM technology in reducing seismic risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BIM features that contain structural and non-structural details concurrently with the use of the fragility curve are very important for building loss assessment (Charalambos et al , 2014; Xu et al , 2019a). For example, a study by Angulo et al (2020) shows that the impact of an earthquake on a building can be determined whether the building can be repaired or demolished. Consequences of losses can also be calculated, such as repair costs, repair time, number of injuries and casualties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seismic monitoring is an important subject all over the world that is facilitated by using BIM modelling for controlling defects in structural and non-structural components [ 172 , 173 , 174 ]. BIM can improve the damage detection and rehabilitation process after an earthquake and improve cost estimation and time consideration in the upper dimension of post-earthquake BIM models [ 175 , 176 ].…”
Section: Content Analysismentioning
confidence: 99%